Proceedings of the Thirty-First International Joint Conference on Artificial Intelligence 2022
DOI: 10.24963/ijcai.2022/15
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Distance Measures Among Elections

Abstract: Motivated by putting empirical work based on (synthetic) election data on a more solid mathematical basis, we analyze six distances among elections, including, e.g., the challenging-to-compute but very precise swap distance and the distance used to form the so-called map of elections. Among the six, the latter seems to strike the best balance between its computational complexity and expressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Intuitively, the isomorphic swap distance between two elections is the summed swap distance of their votes, provided we first rename the candidates and reorder the votes to minimize this value. Maps of elections could be generated using the isomorphic swap distance instead of the positionwise one, and they would be more accurate than those based on the positionwise distance [Boehmer et al, 2022b], but the isomorphic swap distance is NP-hard to compute and challenging to compute in practice [Faliszewski et al, 2019]; indeed, we use a brute-force implementation. Boehmer et al [2022b] have shown that the largest isomorphic swap distance between two elections with m candidates and n voters is 1 4 n(m 2 −m) (up to minor rounding errors; for this result, see their technical report).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intuitively, the isomorphic swap distance between two elections is the summed swap distance of their votes, provided we first rename the candidates and reorder the votes to minimize this value. Maps of elections could be generated using the isomorphic swap distance instead of the positionwise one, and they would be more accurate than those based on the positionwise distance [Boehmer et al, 2022b], but the isomorphic swap distance is NP-hard to compute and challenging to compute in practice [Faliszewski et al, 2019]; indeed, we use a brute-force implementation. Boehmer et al [2022b] have shown that the largest isomorphic swap distance between two elections with m candidates and n voters is 1 4 n(m 2 −m) (up to minor rounding errors; for this result, see their technical report).…”
Section: Methodsmentioning
confidence: 99%
“…Maps of elections could be generated using the isomorphic swap distance instead of the positionwise one, and they would be more accurate than those based on the positionwise distance [Boehmer et al, 2022b], but the isomorphic swap distance is NP-hard to compute and challenging to compute in practice [Faliszewski et al, 2019]; indeed, we use a brute-force implementation. Boehmer et al [2022b] have shown that the largest isomorphic swap distance between two elections with m candidates and n voters is 1 4 n(m 2 −m) (up to minor rounding errors; for this result, see their technical report). Whenever we give an isomorphic swap distance between two elections (with the same numbers of candidates and voters), we report it as a fraction of this value.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations